Evaluasi Produktivitas Proses Produksi Anchor Bold melalui Penerapan Objective Matrix (OMAX) di Industri Manufaktur - Sonny Nugroho Aji; Noval Dwy Setiawan; Roberta Heni Anggit Tanisri (Journal of Industrial and Engineering System, 2026)
AJB, as a manufacturing company, has faced difficulties in meeting its production targets for anchor bold despite utilizing various resources such as labor, raw materials, energy, and working hours. This study aims to measure and evaluate production productivity using the objective matrix (OMAX) method and propose improvements through the fishbone diagram and 5W+1H approach. Data were collected from January to December 2023, covering inputs of materials, labor, energy, and production outputs. Results indicate fluctuating productivity levels, peaking in November (98%) and dropping in August (-39%). Key factors reducing productivity include raw material delays, energy waste, ineffective operators, and inefficient workspace layout. This studi contributes an applicable productivity evaluation model for manufacturing industries.